THE EFFECTIVENESS OF TRANSLATION PRODUCED BY FACEBOOK - Ika Oktaria Cahyaningrum; Widyashanti K Anindita (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The development of technology, especially social media, is very advanced and fast, from various types of social media that exist today such as YouTube, Tiktok, Instagram, Twitter, Whattsap, Line, and others, Facebook entered the early generation after Friendster as a popular social media and inundated by a large following. Facebook updates are also contained in the presentation content, namely Translation for Post, where there is a translation that will automatically appear according to the language settings they choose. There are several translations with inaccurate translation quality so that the researcher makes this problem the object of research. The method used is descriptive qualitative, where the researcher conducts an in-depth analysis of the translation produced in the Translation for Post application on Facebook. The researcher continues previous research, namely a comparative study on comparing the quality of translations in the online apllication. In this study, several problems were found in this study with a moderate level of accuracy, but the acceptance is still well for the target language. Researcher concluded that Translation for Post on Facebook has a better level of translation quality than other online translation applications